Além do arco-íris: tentativa de suicídio entre a população LGBTI+, uma compreensão fenomenológico-hermenêutica - Silva, Maria Vanessa Morais da (Universidade Federal do Rio Grande do Norte, 2022)
Suicide rates around the world differ based on cultural, regional and sociodemographic aspects, as well as the way these deaths are recorded and the extreme underreporting. Despite its high rates, suicide is still seen as taboo, and for some groups it is also an invisible phenomenon. The World Health Organization identifies some groups most vulnerable to the risk of suicide. The LGBTI+ population (Lesbians, Gays, Bisexuals, Transvestites, Transsexuals, Intersex) has been identified as being more prone to suicidal ideation and attempts than their heterosexual peers. This fact is associated with different factors such as prejudice, discrimination, violence and social stigma. This research aims to reflect and understand the experience of LGBTI+ people who have attempted suicide, from a phenomenological-hermeneutic perspective guided by the Heideggerian ontology. Two people who attempted suicide were interviewed, a lesbian woman and a gay man. The analysis of the narrative interviews was based on the understanding and interpretation of the participants' experiences and the researcher's affectations, having as inspiration the Heideggerian hermeneutic circle. The results of this study show the meanings of wanting to die for LGBTI+ people. In this direction, the interpretations of the narratives demonstrate experiences of suffering, fear, misunderstanding, violence, escape from oneself, oppression, a life without place, an existence without belonging and killing oneself as a possibility of no longer living in this world. We reflect on our historical horizon and what it is like to inhabit for this population, as well as the daily resistance to remain in existence. It is hoped that the research results can contribute to broaden the discussion on mental health and suicide of the LGBTI+ population and shed light on the problems experienced by this population in Brazilian society, also collaborating to think, tension and build affirmative public policies.
Keywords: Suicídio; População LGBTI+; Pesquisa fenomenológica; CNPQ::CIENCIAS HUMANAS::PSICOLOGIA